(untitled) (Global Journal of Science Frontier Research, 2018)
Considering gravitation as magnetic binding of (e-p) pairs, galactic systems are described in a fundamental theory based on a QED like Lagrangian with fermions coupled to boson fields. In this formalism severe boundary conditions have to be fulfilled, related to geometry, momentum and energy-momentum conservation. In this way all needed parameters are determined; thus giving rise to a description based on first principles. The primary process is magnetic binding of (e-p) pairs, leading to a very small binding energy of about 3 10 −38 GeV and a first-order equivalent coupling constant, which is in agreement with Newton’s gravitational constant ttN. Systems of magnetic binding of 10∼100 (e-p) pairs (or hydrogen atoms) are related to galaxies. However, creation of stable galactic systems has been possible only under extreme conditions: a strongly reduced attractive force and heating, both arising from the annihilation of a large part of matter during a cosmic phase of high density. With these requirements, rotation velocities of galaxies are well described, yielding information on the average particle density and M gr ∼ v2R/ ttN derived from gravitation theory, the deduced galaxy masses show a rapid fall-off to smaller radii, which can be understood by the finiteness of these systems. No evidence has been found for galactic dark matter contributions